Studies on the Effect of Split Application of NPK fertilizers on Yield and Quality of Papaya (Carica papaya L.) under Central Dry Zone of Karnataka - Rammohan, Yellapu; Shivakumar, B. S.; Dinesh, Kumar M.; Thippesh, D.; Salimath, Sarvajna B. (International Journal of Bio-resource and Stress Management, 2025)
The experiment was conducted from October, 2020 to July, 2021 at Eswargere village in the Chitradurga district of Karnataka, India to evaluate the impact of split applications of nitrogen, phosphorus, and potassium (NPK) fertilizers on the growth, yield, and quality of papaya. The study utilized a Randomized Complete Block Design (RCBD), incorporating seven distinct treatments. These treatments included varying rates of fertilizer application 75%, 100%, and 125% of the recommended dose of fertilizers (RDF) and different application frequencies, either bimonthly or monthly. This design aimed to determine the most effective fertilizer rates and timing to optimize papaya production and quality under local agronomic conditions. Among yield and yield attributes fruit length (23.54 cm), fruit diameter (14.36 cm), number of fruits plant-1 (30.85), fruit weight (1.46 kg), total fruit yield (138.83 t ha-1) were recorded maximum in 125% RDF through split application. The maximum total soluble solids (13.45°Brix), reducing sugars (10.10%), non-reducing sugars (2.68%), total sugars (12.97%) and minimum acidity (0.014%) were also found in 125% RDF through split application. The results were on par with 100% RDF through split application treatment. So, the application of 100% RDF through split at different growth stages (150:125:100 N:P2O5:K2O g plant-1) in vegetative stage of 4 months, (50:100:150 N:P2O5:K2O g plant-1) in flowering to fruit set stage of 2 months, (50:25:250 N:P2O5:K2O g plant-1) in fruit development stage of 3 months at monthly interval proved to be promising for fetching higher yield and good quality of papaya fruits.